PEMBELAJARAN IPA BERBASIS ETNOSAINS DALAM TINJAUAN FILSAFAT - Nadia Kurnia Ningsih; Muhammad Nurwahidin; Sudjarwo Sudjarwo (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
Ethnoscience is a learning that describes cultural values ​​(original science) as a form of natural phenomena that grow in the community and the truth can be studied empirically. Ethnoscience raises local wisdom and cultural understanding as objects of study in science learning which will then be scientifically tested into science learning in schools. The purpose of this study is to examine philosophy in the aspects of ontology, epistemology, and axiology of ethnoscience studies in science learning. This study uses the "literature review" method. The data collection techniques are sourced from various reference articles in 2018-2022 from Google Scholar and relevant books. In the review of the ontology aspect, it examines the nature of ethnoscience-based science learning, epistemology includes how to use ethnoscience as a scientifically identifiable learning resource, while the axiological aspect examines the relevance of ethnoscience-based science learning that has cultural character values ​​so that science can be useful in the environment. community and in the student's school environment